Effect of Praziquantel on Preventing Delayed Infection of Schistosoma japonicum in Buffaloes and Goats - Xiang Gui; Bing Shao; Haoran Zhong; Rongxue Lv; Hao Li; Ke Lu; Yang Hong; Zhiqiang Fu; Zhenjie Lu; Mengge Xu; Yamei Jin; Jinming Liu (Microorganisms)
Schistosomiasis, caused by Schistosoma japonicum, continues to pose a major public health threat in East Asia, with an estimated 71 million people at risk of infection. Domestic animals, especially buffaloes and goats, serve as important reservoir hosts, facilitating the transmission of the parasite to humans. While praziquantel (PZQ) is the first-line treatment for schistosomiasis due to its broad-spectrum efficacy against adult schistosomes, its prophylactic potential is less explored. This study aimed to evaluate the efficacy of PZQ in preventing S. japonicum infection in buffaloes and goats via assessing worm burden, worm size, hematological changes, and immune modulation. In the present study, buffaloes and goats were pretreated with PZQ at various doses (7–25 mg/kg body weight), followed by infection with S. japonicum cercariae. The results showed significant reductions in total worm burden and female worm burden, with one oral administration at 13 mg/kg for buffaloes and one injection at 25 mg/kg for goats offering the most robust protection. Worm length was also significantly reduced in both buffaloes and goats, indicating that PZQ not only prevented infection in this study but also inhibited worm growth. Furthermore, PZQ pretreatment modulated immune responses, as evidenced by increased levels of nitric oxide (NO) and interleukin-2 (IL-2) in buffaloes and Lym% in goats. These findings suggest that PZQ has significant prophylactic potential in livestock, offering a practical solution for reducing schistosome transmission from animals to humans in endemic regions. Additionally, this study indicates that PZQ pretreatment does not contribute to resistance development, as newly established infections are effectively cleared during the initial treatment window.